Cyclopentenone Prostaglandins: Biologically Active Lipid Mediators Targeting Inflammation - Lee, Bohae Rachel; Paing, May Hnin; Sharma-Walia, Neelam (Frontiers in Physiology, 2021)
Cyclopentenone prostaglandins (cyPGs) are biologically active lipid mediators, including PGA2, PGA1, and PGJ2. cyPGs are important regulators of inflammation, cell proliferation, apoptosis, angiogenesis, cell migration, stem cell activity. cyPGs biologically act on multiple cellular targets, including transcription factors and signal transduction pathways. cyPGs regulate the inflammatory response by interfering with NF-κB, AP-1, MAPK, and JAK/STAT signaling pathways via both a group of nuclear receptor proliferator-activated receptor-γ (PPAR-γ) dependent and PPAR-γ independent mechanisms. cyPGs have been studied in the context of chronic inflammation that is a causative factor in various cancers, also in the case of host-pathogen (bacterial, viral, parasitic) interaction mediated inflammation. Their anti-proliferation, pro-apoptosis, cytoprotective stress response, antioxidant, anti-angiogenic, and anti-metastatic activities allow them to interfere with tumor and cancer development to infections or other factors. cyPGs exhibit potent effects on viral infections by repressing viral protein synthesis, altering viral protein glycosylation, inhibiting virus transmission, and reducing virus-induced inflammation. Because of these activities, cyPGs have significant therapeutic value, especially in resolving inflammation and could be used in adjunct with other existing therapies.